Perioperative Inflammatory Response in Total Knee Arthroplasty Patients: Impact of Limb Preconditioning. Issue 5 (1st August 2010) - Memtsoudis, Stavros G.; Della Valle, Alejandro Gonzalez; Jules-Elysse, Kethy; Poultsides, Lazaros; Reid, Shane; Starcher, Barry; Ma, Yan; Sculco, Thomas P.
Abstract : Background and Objectives: Ischemic preconditioning of tissue that is to undergo procedure-induced underperfusion has been used in a number of surgical settings to reduce the subsequent inflammatory response and its sequelae. The objective of this prospective, randomized study was to evaluate the effect of ischemic preconditioning on the systemic inflammatory response, degree of lung catabolism, and postoperative pain associated with total knee arthroplasty (TKA). Materials: Thirty-four patients undergoing unilateral TKA under tourniquet ischemia were enrolled with half (n = 17) being randomized to an episode of limb preconditioning before induction of ischemia for surgery. Markers of inflammation (interleukin 6 [IL-6], C-reactive protein, tumor necrosis factor α, and leukocyte count) and elastin catabolism (desmosine) were measured at baseline and various points postoperatively. Pain scores and length of stay were recorded. Results: A significant increase in the levels of IL-6, C-reactive protein, tumor necrosis factor α, and white blood cell count was observed after surgery in both groups. Despite trends toward decrease in the IL-6 level in the preconditioning group, no significant difference between groups was observed for all markers at any given time point. Urine desmosine-creatinine ratios did not differ between groups, and no significant changes from baseline were seen postoperatively. However, median pain scores and length of hospital stay were lower in the treatment group. Conclusions: Preconditioning of the lower extremity in the setting of TKA under regional anesthesia may have limited value in reducing the systemic inflammatory response and level of lung injury. However, preconditioning may be associated with beneficial effects such as reduction in postoperative pain levels, and thus, further investigations are warranted.